2003
DOI: 10.1023/b:phot.0000011952.77340.53
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Partitioning and Assimilation as Affected by Nitrogen Deficiency in Cassava

Abstract: Plants of cassava (Manihot esculenta Crantz) were raised in a sand root medium watered with nutrient solutions, under greenhouse conditions. As the N-supply increased, shoot dry mass was enhanced to a greater extent than root dry mass, thus leading to an increased shoot to root ratio. In leaves, contents of total soluble saccharides, non-reducing saccharides, and inorganic phosphate increased linearly with increasing N-supply. An opposite response was found for reducing saccharides and starch. In general, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…Another important aspect, as deduced from a lower HI, is that the tuberous roots' ability to metabolize sucrose unloaded from phloem could have been impaired, leading sugar accumulation in the source leaves, which can determine photosynthesis inhibition, a process known as "photosynthetic repression feedback". This has already been observed in cassava by Cruz, Mosquim, Pelacani, Araujo, and DaMatta (2003). Albacete et al (2014) also indicated that the reduction in sink activity might be an indirect effect of salinity on A.…”
Section: Gas Exchangessupporting
confidence: 57%
“…Another important aspect, as deduced from a lower HI, is that the tuberous roots' ability to metabolize sucrose unloaded from phloem could have been impaired, leading sugar accumulation in the source leaves, which can determine photosynthesis inhibition, a process known as "photosynthetic repression feedback". This has already been observed in cassava by Cruz, Mosquim, Pelacani, Araujo, and DaMatta (2003). Albacete et al (2014) also indicated that the reduction in sink activity might be an indirect effect of salinity on A.…”
Section: Gas Exchangessupporting
confidence: 57%
“…Further, high N concentration also increases the concentration of cyanogenic glucosides in the root while decreasing starch (Obigesan & Fayemi, 1976;Howeler, 2002). The N use efficiency, but not yield, of cassava is often highest when plants are grown on soils with low N (Cruz et al, 2003). Several of the approaches discussed in the previous sections on improving photosynthetic efficiency would also increase N use efficiency, thus increasing production without the need for more N fertilizer .…”
Section: Reviewmentioning
confidence: 99%
“…This could be an adaptive response of the chloroplast to increase photosynthetic area and maintain photosynthetic rate under slight Zn deficiency. In the RL, owing to the damage of chloroplast membrane and extensive disorganization of thylakoids, the sucrose produced by chloroplast photosynthesis fails to be transported out of the cell (Cruz et al, 2003), thus, starch accumulated in the chloroplasts (Table 3, Fig. 3C, F and I), forming larger starch grains and depressing the feedback of Pn (Nafziger and Koller, 1976).…”
Section: Type Of Leavesmentioning
confidence: 99%